Readiness for and Response to Coronavirus Disease 2019 Among Pediatric Healthcare Providers: The Role of Simulation for Pandemics and Other Disasters*. Issue 6 (June 2021) - Wagner, Michael; Jaki, Christina; Löllgen, Ruth M.; Mileder, Lukas; Eibensteiner, Fabian; Ritschl, Valentin; Steinbauer, Philipp; Gottstein, Maximilian; Abulebda, Kamal; Calhoun, Aaron; Gross, Isabel T.
Abstract : OBJECTIVES: Early preparation for the training and education of healthcare providers, as well as the continuation or modification of routine medical education programs, is of great importance in times of the coronavirus disease 2019 pandemic or other public health emergencies. The goal of this study was to characterize these self-reported efforts by the pediatric simulation community. DESIGN: This was a global, multicenter survey developed via a Delphi process. SETTING: International survey study. SUBJECTS: The survey was sent to 555 individual members of the three largest international pediatric simulation societies (The International Pediatric Simulation Society, International Network for Simulation-based Pediatric Innovation, Research & Education, and Netzwerk Kindersimulation e.V.) between April 27, 2020, and May 18, 2020. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Description of coronavirus disease 2019 pandemic simulation-based preparation activities of pediatric acute and critical care healthcare providers. The Delphi process included 20 content experts and required three rounds to reach consensus. The survey was completed by 234 participants (42.2%) from 19 countries. Preparation differed significantly between the geographic regions, with 79.3% of Anglo-American/Anglo-Saxon, 82.6% of Indian, and 47.1% of European participants initiating specifically coronavirus disease 2019-related simulation activities. Frequent modifications to existing simulation programs included the use of telesimulation and virtual reality training. Forty-nine percent of institutions discontinued noncoronavirus disease 2019-related simulation training. CONCLUSIONS: The swift incorporation of disease-specific sessions and the transition of standard education to virtual or hybrid simulation training modes occurred frequently. The approach used, however, depended heavily on local requirements, limitations, and circumstances. In particular, the use of telesimulation allowed education to continue while maintaining social distancing requirements. Abstract : Supplemental Digital Content is available in the text.